NANOTECHNOLOGY: EMERGING PROSPECTS, APPLICATIONS, AND INNOVATIONS - Vijay Krishanan; Kiran kumar,S; Karthick K; Sindhuja, A; Kotteswari K (The Bioscan, 2025)
Nanotechnology operates at the scale of one-half the diameter of DNA to 1/20 the size of a red blood cell, offering unique physicochemical properties such as increased surface area to volume ratio and enhanced reactivity. These characteristics make nanoparticles particularly useful in diverse domains, especially biomedical applications including targeted drug delivery, diagnostics, and imaging. This review highlights the synthesis, characterization, and biomedical implications of metallic and metal oxide nanoparticles, emphasizing recent trends and eco-friendly synthesis routes like green synthesis. The multifaceted nature of nanotechnology continues to open novel frontiers in science, medicine, and environmental applications.